Exploring Semantic Discrepancies of Selected Religious Terminologies in English and Arabic - Dhayef, Qasim Abbas; Kareem, Thamir Muhammad (RIRAI Publisher, 2025)
This research tries to examine the semantic discrepancies of religious terms in both English and Arabic, concentrating on the implications of such differences for translation, intercultural communication, and understanding of such terms. Religious terminology often symbolizes deep cultural, historical, and theological nuances, which can lead to divergent interpretations when translated between these two languages. The study adopts a contrastive semantic analysis approach, identifying key terms within Islamic and Christian traditions, and analyzing their linguistic, contextual, and cultural dimensions. It highlights how religious terms in Arabic could carry layered meanings that are not fully captured by their English counterparts. Conversely, English religious terms might encompass theological connotations that may lack equivalent expressions in Arabic. This paper aims to provide insights into the difficulties of religious translation to shed light and address these semantic gaps, fostering better intercultural understanding and preserving the integrity of the original terms.